STRATEGI PEMBERDAYAAN BURUH MIGRAN PEREMPUAN INDONESIA DI HONGKONG - Wulan, Tyas Retno; Kolopaking, Lala M.; Wahyuni, Ekawati Sri; Abdullah, Irwan (Jurnal AGRISEP, 2009)
Social remittances (ideas, system practice, and social capital flow from the receiving country to the home country) of Indonesian female migrant workers (BMP) in Hong Kong appeared better and more complete than other BMP in other countries like Malaysia, Saudi Arabia, or Singapore.  Based on that research, we are encouraged to do extensive research in order to identify factors  that push  BMP’s social remittances development  in Hong Kong, to identify kinds of social remmitances they receive  and to understand on how far their social remittances become a medium to empower them and their society.  This study is done in qualitative method that uses an in-depth interview technique and FGD.  Subjects of study are BMP, the government (Ministry of Manpower and Transmigration and BNP2TKI), NGOs, migrant workers’ organization and researchers of BMP. The study done in Cianjur (West Java), Wonosobo and Banyumas (Central Java) and Hong Kong indicates that during their migration process, female migrant workers not only have economical remittance that can be used for productive activities, but also social remittances.  The social remittances are in the form practical knowledge such as language skill and nursery; knowledge on health, financial management; ethical work; the mindset changing and networking. The study  indicate that female migrant workers are extraordinary women more than just an ex-helper.  Their migration has put them into a position as an agent of development in society.